2015
DOI: 10.3109/10826084.2015.1018541
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Moral Disengagement in Underage Drinking and Heavy Episodic Drinking

Abstract: Understanding how adolescents self-regulate their drinking, and ways that such self-regulation may be deactivated or disengaged, may help identify those adolescents at increased risk of drinking underage and of engaging in heavy episodic drinking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 63 publications
1
5
0
2
Order By: Relevance
“…Thus, we found no support for the notion that moral disengagement is activated as post-hoc rationalisations for existing behavioural inclinations to harass. This finding is consistent with longitudinal studies that also found no evidence of moral disengagement as a direct consequence of morally transgressive behaviour such as bullying (Sticca & Perren, 2015), and underage drinking (Quinn & Bussey, 2015a).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Thus, we found no support for the notion that moral disengagement is activated as post-hoc rationalisations for existing behavioural inclinations to harass. This finding is consistent with longitudinal studies that also found no evidence of moral disengagement as a direct consequence of morally transgressive behaviour such as bullying (Sticca & Perren, 2015), and underage drinking (Quinn & Bussey, 2015a).…”
Section: Discussionsupporting
confidence: 89%
“…Stanger et al (2013), for example, observed that low anticipatory guilt mediated the positive link between moral disengagement and males' selfreported likelihood to aggress in sport. Similarly, Quinn and Bussey (2015a) found that mediation of anticipatory guilt in the relationship between moral judgment and adolescents' to women who are seen to violate traditional gender ideals (e.g., Berdahl, 2007aBerdahl, , 2007bHolland & Cortina, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Desde entonces han sido diversos los campos de estudio en los que se ha demostrado la incidencia de la desconexión moral con diversos comportamientos transgresores, entre ellos, el terrorismo y las actividades bélicas (Bandura, 1988;Villegas de Posada, Flórez & Espinel, 2018;Bandura, 2004;Osofsky, Bandura & Zimbardo, 2005), el consumo de drogas y alcohol (Quinn & Bussey, 2015b, 2015aGiulio et al, 2018), la propensión de los niños a decir mentiras (Doyle & Bussey, 2017), el uso de esteroides en el deporte (Lucidi et al, 2008;Boardleya et al, 2018), el rol de la parentalidad en la desconexión moral en la niñez (Campaert, Nocentini & Menesini, 2018;Hyde, Shaw & Moilanen, 2010;Houwing & Bussey, 2017) y, en especial, las actividades delictivas en jóvenes (Giulio et al, 2018;DeLisi et al, 2014;Petruccelli et al, 2017), siendo este último un campo de estudio reciente con múltiples aristas por explorar.…”
Section: Mécanismes De Déconnexion Morale Et Sa Relation Avec L'empatunclassified
“…Increased MD has been associated with a range of relevant behaviours, including ethical consumer choices, greater propensity of (adolescent) alcohol and other drug use; sports doping; use of cognitive enhancers in educational settings; criminal behaviour, and violent offending (Boardley et al, 2017;Chowdhury & Fernando, 2014;Graça et al, 2014;Heyes & Boardley, 2019;Ishoy, 2017;Jang, 2019;Newton, Barrett, et al, 2014;Passini, 2012;Quinn & Bussey, 2015a, 2015bWojciechowski, 2021). For example, Boardley et al (2017) found that MD in relation to sports and gym doping negatively predicted anticipated guilt, and positively predicted reported doping.…”
Section: Introductionmentioning
confidence: 99%